AN ANALYSIS OF SUBTITLING STRATEGIES OF IDIOMATIC EXPRESSIONS IN THE FILM ENTITLED "THE AVENGERS" - Ismail, Ganjar (2014)
This research is entitled "An Analysis of Subtitling Strategies of Idiomatic Expressions In the Film Entitled 'The Avengers'." The research uses a qualitative and descriptive method. The research employs Hockett's theory of idiomatic expressions (1958) to classify idioms found on the film and Gottlieb's theory of subtitle strategies (1994) to analyze the subtitle strategies used in subtitling the idioms. The findings show there are 684 sentences and phrases that can be categorized as the data with the total idioms are 781. All six types of idiomatic expressions are available on the data. The most frequent type of idiom found is substitute (47,5 %), whereas figure of speech and abbreviation are the least common type with only 2,82% of each type. Moreover, there are nine of ten subtitle strategies empoyed in subtitling the idioms, namely: expansion, transfer, paraphrase, imitation, transcription, dislocation, condensation, decimation and deletion. The most frequent strategy employed is transfer (28,81%) and the least employed strategy is transcription (0,26%). The findings also show the translator has a tendency to apply tansfer in translating substitutes (47,17%) and abbreviations (27,27%), imitation in translating propper names (47,29%), and paraphrase in translating English phrasal compounds (48,24%), figures of speech (86,36%) and slangs (70,51%). This research is entitled "An Analysis of Subtitling Strategies of Idiomatic Expressions In the Film Entitled 'The Avengers'." The research uses a qualitative and descriptive method. The research employs Hockett's theory of idiomatic expressions (1958) to classify idioms found on the film and Gottlieb's theory of subtitle strategies (1994) to analyze the subtitle strategies used in subtitling the idioms. The findings show there are 684 sentences and phrases that can be categorized as the data with the total idioms are 781. All six types of idiomatic expressions are available on the data. The most frequent type of idiom found is substitute (47,5 %), whereas figure of speech and abbreviation are the least common type with only 2,82% of each type. Moreover, there are nine of ten subtitle strategies empoyed in subtitling the idioms, namely: expansion, transfer, paraphrase, imitation, transcription, dislocation, condensation, decimation and deletion. The most frequent strategy employed is transfer (28,81%) and the least employed strategy is transcription (0,26%). The findings also show the translator has a tendency to apply tansfer in translating substitutes (47,17%) and abbreviations (27,27%), imitation in translating propper names (47,29%), and paraphrase in translating English phrasal compounds (48,24%), figures of speech (86,36%) and slangs (70,51%).